Adrenocorticotropic hormone-secreting phaeochromocytoma as a cause of treatment-resistant hypertension and recurrent pulmonary emboli - Vollmer, Shobitha ; 0000-0002-7211-087X; Borg, Henrik (Journal of the Royal College of Physicians of Edinburgh, 2023)
We report an unusual case of a patient presenting with Cushing’s syndrome caused by a phaeochromocytoma secreting adrenocorticotropic hormone (ACTH). The patient had a history of treatment-resistant hypertension, secondary amenorrhoea and tendency towards hypokalaemia. She had multiple signs of Cushing’s syndrome, such as swelling, bruising, abdominal striae and proximal myopathy. Hypokalaemia is more common in patients with ectopic ACTH-secretion than other causes of Cushing’s syndrome. Computed tomography, adrenal vein sampling and biochemistry could confirm an ACTH-secreting phaeochromocytoma. It is important to consider that hypersecretion of more than one hormone may exist in a unilateral adrenal adenoma. This patient also presented with recurrent pulmonary emboli, and there is an increased risk of venous thromboembolism in patients with ACTH-secreting phaeochromocytoma. Anticoagulation should be considered for as long as the disease is active. We demonstrate that unilateral adrenalectomy can be curative in patients with ACTH-secreting phaeochromocytoma.
Publisher Copyright: © The Author(s) 2023.
Keywords: ACTH-secreting phaeochromocytoma; Cushing’s syndrome; phaeochromocytoma